2011
DOI: 10.1124/mol.111.073528
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: New Players in Cardiac Injury and Protection

Abstract: MicroRNAs (miRNAs) have emerged as a novel class of endogenous, small, noncoding RNAs that negatively regulate gene expression via degradation or translational inhibition of their target mRNAs. Over 700 miRNAs have been identified and sequenced in humans, and the number of miRNA genes is estimated at more than 1000. Individual miRNA is functionally important as a transcription factor because it has the ability to regulate the expression of multiple genes through binding to its target with imperfect or perfect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 86 publications
1
85
0
4
Order By: Relevance
“…IR stimuli alter the expression of microRNAs. 94 Recent studies revealed that microRNAs are implicated in cardiac pathology including hypertrophy and failure 95 and IR injury 96 (Table 2). Therefore, microRNAs are novel promising therapeutic targets for IHDs.…”
Section: Future Directionsmentioning
confidence: 99%
“…IR stimuli alter the expression of microRNAs. 94 Recent studies revealed that microRNAs are implicated in cardiac pathology including hypertrophy and failure 95 and IR injury 96 (Table 2). Therefore, microRNAs are novel promising therapeutic targets for IHDs.…”
Section: Future Directionsmentioning
confidence: 99%
“…MicroRNAs fundamentally influence the pathogenesis of various events (Kukreja et al 2011), including adverse cardiac remodelling such as hypertrophy and fibrosis (van Rooij et al 2012). These myocardial alterations compromise cell-to-cell contacts and Cx43 channels mediated communication in diseased or aged heart and promote the occurrence of malignant arrhythmias (Tribulova et al 2008;Jansen et al 2012;Radosinska et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Újabb vizsgálatok szerint legalább 20 mikro-RNS szintje mutat összefüg-gést az AMI-val és ezekből legalább 9 a troponinszintekkel [34]. A miR-1, miR-133, miR-208 és a miR499 a legjobban tanulmányozott molekulák koszorúér-betegségekben és akut myocardialis infarctusban [35]. A sérült myocardiumból kiáramló mikro-RNS-ek mellett az akut esemény után emelkedett szintet mutató miRNS-ek részben extracardialis eredetűek, mint például a miR30c, miR-145, amelyek ugyanakkor összefüggést mutattak az infarktus méretével.…”
Section: Akut Myocardialis Infarctusunclassified